Molecular mechanisms of idiopathic pulmonary fibrosis: Emerging therapeutic approaches - Araujo, Victoria Souza; Siqueira, Andréa Maria de Paula; Teixeira, Carlos Santos; Serafim , Edilma Casimiro Gomes; Gregório , Élida Maria Silva; Mello , Ihury Garofo Kennedy Anunciação de; Mello , Ithalo Garofo Kennedy Anunciação de; Laudelino, Jadson Soares; Costa, Safira Monteiro; Mororó, Silvia Helena Varela (Seven Editora, 2024)
Idiopathic Pulmonary Fibrosis (IPF) stands as one of the most puzzling interstitial lung diseases within respiratory medicine, marked by a relentless progression that impairs lung function. Despite its elusive etiology, recent breakthroughs in molecular biology and genomics have granted a deeper understanding of the intricate cellular and molecular pathways implicated in its pathogenesis. This paper seeks to provide a comprehensive and up-to-date insight into these molecular mechanisms, emphasizing their significance in the development of novel therapeutic approaches and intervention strategies aimed at curbing the disease's progression and enhancing the life quality of affected patients.. DOI: https://doi.org/10.56238/sevened2023.007-033